Embracing difference: on law, code and space - Tedeschi Miriam (Routledge, 2025)
This article explores the ontogenesis of software (code) and law and how they are entangled and in-form bodies and urban space. Herein, I investigate how this process of in-forming creates ruptures, differences in the otherwise smooth experience of the urban. These remain largely invisible but surface when interruptions in the everyday use of technologies affect urbanites. These interruptions might be data breaches, frauds, invasive phishing emails and the likes. Information and affect play a key role as posthuman elements in the ontogenesis. Ruptures, differences may also open up lines of flight and resistance that highlight differences rather than conceal them. Taking an ontogenetic and new materialist perspective, this paper contributes to strengthening the theoretical dialogue between law, the science of space (geography) and philosophies of technology.